Sri Lanka : Third Review under the Extended Arrangement under the Extended Fund Facility and Request for Modification of Performance Criterion-Press Release; Staff Report; and Statement by the Executive Director for Sri Lanka. (IMF Staff Country Reports; Country Report, 2018)
This paper discusses Sri Lanka's Third Review Under the Extended Arrangement Under the Extended Fund Facility and Request for Modification of Performance Criterion (PC). Performance under the program has remained broadly on track since the second review despite a series of weather-related supply shocks. All end-June and continuous PCs are met. Revenue mobilization has helped meet the quantitative fiscal targets, while strong capital inflows have supported the buildup of international reserves. The budget targets a primary surplus of 1 percent of GDP and frontloads fiscal consolidation toward the authorities' objective of reducing the overall fiscal deficit to 3.5 percent of GDP by 2020.